Plasma androgens and the presence and course of depression in a large cohort of men. (August 2021) - de Wit, Anouk E.; Giltay, Erik J.; de Boer, Marrit K.; Nolen, Willem A.; Bosker, Fokko J.; Penninx, Brenda W.J.H.; Schoevers, Robert A.
Abstract: Background: Hypoandrogenic men showed a higher prevalence of major depressive disorder (MDD), which could be ascribed to overlapping symptoms such as sexual dysfunction, or additionally to core emotional symptoms such as sadness and anhedonia. We examined whether androgen levels 1) differ between men with and without MDD cross-sectionally, 2) are associated with an elevated risk for onset of MDD prospectively, and 3) associate with all individual MDD symptoms, or only with hypogonadism overlapping symptoms. Methods: In 823 men (mean age 43.5 years), baseline plasma levels of total testosterone, 5α-dihydrotestosterone (5α-DHT), and androstenedione were determined with liquid chromatography–tandem mass spectrometry, and dehydroepiandrosterone-sulphate (DHEAS) and sex hormone binding globulin with radioimmunoassay, whereas free testosterone was calculated. MDD status was assessed at baseline and after two years using structured interviews and individual MDD symptoms were self-rated at baseline, and after one and two years. Results: None of the androgen levels were associated with current or onset (incidence or recurrence) of MDD. Free testosterone was only inversely associated with interest in sex. Also, androstenedione and DHEAS were positively associated with some individual MDD symptoms, and 5α-DHT levels showed non-linear associations (both with low and high levels) with MDD symptom severity and several individual MDD symptoms. Conclusions: These results support the idea that circulating androgens synthesised by the testes are of limited clinical relevance to MDD in adult men, but levels of androstenedione, DHEAS and 5α-DHT may be associated with some individual MDD symptoms. Highlights: Associations between androgens and depression were examined in 823 adult men. None of the androgen levels were associated with current or future depression. Free testosterone was only inversely associated with interest in sex. Androstenedione, dehydroepiandrosterone-sulphate, and 5a-dihydrotestosterone were linked to several symptoms. This suggests that androgens have limited clinical relevance in depression in men.